1999
DOI: 10.1177/1081180x9900400403
|View full text |Cite
|
Sign up to set email alerts
|

Party Competition on the Internet in the United States and Britain

Abstract: This article examines the prominence of Web sites of major and minor parties in the United States and the United Kingdom, comparing features such as search capabilities, membership forms, information on party organization and issues, characteristics of graphics, and currency of updates as well as their relative quality and sophistication.We also look at the prominence of major and minor parties in newspapers and magazines and in various search engines and sites for political junkies. We find that minor parties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 3 publications
(1 reference statement)
3
63
0
5
Order By: Relevance
“…While not the most important communication outlet, all parties and politicians increasingly utilize the World Wide Web (Gibson and Ward 2000;Margolis et al 2001) The website offers elected representatives a space to present themselves to their constituents. The website, to use Goffman's phrase, constitutes another 'front region' in which representatives disclose information about themselves that would not necessarily be exposed to another in a face-to-face encounter.…”
Section: Impression Management Onlinementioning
confidence: 99%
“…While not the most important communication outlet, all parties and politicians increasingly utilize the World Wide Web (Gibson and Ward 2000;Margolis et al 2001) The website offers elected representatives a space to present themselves to their constituents. The website, to use Goffman's phrase, constitutes another 'front region' in which representatives disclose information about themselves that would not necessarily be exposed to another in a face-to-face encounter.…”
Section: Impression Management Onlinementioning
confidence: 99%
“…With some exceptions, the tendency of "old" organisations such as trade unions has been to use the Internet as previous media of communication, not fulfi lling its most innovative aspects (such as interactivity; for this see Rättilä in this volume) and using it for top-down forms of communication. Findings like this have been highlighted by different studies concerning the websites of political parties (Margolis et al 1999;Gibson et al 2003) and institutions (Coleman et al 1999;Trechsel et al 2003). This evidence raises the question of whether old organisations jumping online are reproducing on the Internet their vertical styles of communication.…”
Section: The Two Sides Of the Internet: Pros And Cons Of Computer-medmentioning
confidence: 86%
“…However, Margolis et al (1999) found that the two major parties in the US had more extensive websites and received more attention on the web than minor parties.…”
Section: Adaptation Thus Farmentioning
confidence: 96%